Guide memoire: The principles of reasonable prospects for eventual economic extraction - T. Mapeta; S. M. Rupprecht (The Southern African Institute of Mining and Metallurgy, 2025)
Discussions on reasonable prospects for eventual economic extraction (RPEEE) include the CRIRSCO 2019 reporting template, JORC 2012, SAMREC 2016, CIM 2019 Guideline, and Regulation SK-1300. These reporting codes all conform to the principles of reasonable prospects for eventual economic extraction. To demonstrate that all mineral resources align with the RPEEE principles, the Competent Person is responsible for endorsing the mineral resource estimate. Moreover, establishing mineral resources and RPEEE requires technical input from numerous technical specialists, such as mining and geotechnical engineers, metallurgical engineers, social and environmental specialists, financial and governmental practitioners, and more. The aim is to improve the transparency of the disclosure of mineral resources and guarantee the investor or potential investor that the reporting of mineral resources is based on reliable technical, economic, environmental, social, and other relevant factors. This paper discusses the important protocols and definitions in some international reporting codes for the purposes of developing a guide memoire that will assist the Competent Person to interpret, establish and apply RPEEE appropriately and easily.